(3GdJLQHI GdSjGSjI ddMQcI GdESdGejI GdeYGUQI (B:s (3OQhS GdeGVj hCaGb YKeGf (B/s - (3YKeGf,eMeO aJMj s ((3GdLRGFQ (B:s (3OGQ GdeSJbHd ,s, 1991)
(3jbOe GdcGJH Yf GdJLQHI GdSjGSjI ddMQcI GdESdGejI GdeYGUQI cGf GdcGJH aj Ghd YgOg YXhG aj MQcI GdENhGf GdeSdejf dcfg GNJGQ HYO Pdc GdJaQY ddHMK GdYdej h ddUMGaI GdGSdGejI aOQS aj GdLRGFQ h GdhdGjGJ GdeJMOI GdGeQjcjI h JQCS dYOI SfhGJ JMQQ eLdI CQGHjG GdTgQjI GdJj cGfJ JUOQ aj dfOf h GTJgQ NUhUG HcJGHJg ef Mbhb GdGfSGf aj GdacQ GdSjGSjGdGSdGej h HfXQJg GdfbOjI GdeJLQOI dJGQjN GdMQcI GdESdGejI GdeYGUQIs
Keywords: (3GdOjebQGWjIs; (3Ojf GdESdGes